1996
DOI: 10.3109/01485019608987882
|View full text |Cite
|
Sign up to set email alerts
|

A 20-kDa Protein in Human Seminal Plasma that is Identical to Gross Cystic Disease Fluid Protein 15 and Prolactin-Inducible Protein

Abstract: A new method is described for isolating the 20-kDa protein, which used to be purified using an actin-immobilized column from human seminal plasma. This method employed ion-exchange column chromatography and isoelectric focusing separation. The level of seminal protein was determined by sandwich ELISA to be 1.06 +/- 0.27 mg/mL (mean +/- SD, n = 8). Its cDNA was cloned from a human salivary gland cDNA library by immunoscreening. The 553-nucleotide sequence included the 5' untranslated region and extended to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We report that PIP is expressed in the bovine testis and epididymis as determined by RT-PCR and IHC. Prolactin-inducible protein expression has been observed in the bovine submaxillary gland [23], and PIP has been reported to be expressed in seminal fluid through production in the prostate and seminal vesicles in other species [22,42,43]. We also observed PIP staining in the testis stromal tissues, and colocalization with the PRLR has been determined in the spermatogonia using IHC (data not shown).…”
Section: Discussionsupporting
confidence: 55%
“…We report that PIP is expressed in the bovine testis and epididymis as determined by RT-PCR and IHC. Prolactin-inducible protein expression has been observed in the bovine submaxillary gland [23], and PIP has been reported to be expressed in seminal fluid through production in the prostate and seminal vesicles in other species [22,42,43]. We also observed PIP staining in the testis stromal tissues, and colocalization with the PRLR has been determined in the spermatogonia using IHC (data not shown).…”
Section: Discussionsupporting
confidence: 55%
“…Amino Acid Sequence Analysis of GCDFP-15/PIP from BCF. Although identical cDNA clones have been isolated from a cDNA library derived from steroid-and prolactintreated T47D human breast cancer cell line (2), from a human salivary gland cDNA library (21), and from human seminal vesicles (22), conflicting data at protein level are reported. Analysis of the C-terminus of gp17/SABP from HSP gave a Glu residue (12,20), in contrast to a Val residue for GCDFP-15/PIP from BCF, obtained by Vandewalle et al (23).…”
Section: Resultsmentioning
confidence: 99%
“…17) PIP/gp17 is the major component of seminal plasma that is present in the range of 0.2 to 1 mg/ml, but the physiological importance of production in the prostate is obscure. 3,11) PIP exhibits binding ability to CD4, which is thought to suppress HIV infection. 7) Further, PIP inhibits the growth of Streptococcus in culture by interaction with microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…4) In the human male genital tract, glandular epithelium of the seminal vesicle is the primary source of PIP, but PIP production has not been detected in other organs. 1,[11][12][13] On the other hand, approximately 10% of prostate cancer tissues immunohistochemically react with PIP. 8,14) Hall et al reported that PIP is co-expressed with prostate-specific antigen (PSA), a major prostate cancer marker, in androgen receptor-positive breast tumors.…”
mentioning
confidence: 99%